1995
DOI: 10.1136/jmg.32.7.546
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of genetic heterogeneity in familial psoriasis.

Abstract: Psoriasis affects approximately 2% of the European population and is often familial. Linkage of a subset of psoriasis families to loci on chromosome 17q has recently been reported. We have studied members of a large multiply affected family from the north east of England and analysed genotypes for markers from 17q, including the polymorphic microsateilite markers AFM210xa5, AFM163ygl, AFMO44xg3, AFMa353ygl, and AFM217yd19. Two point and multipoint analysis clearly show exclusion of linkage between the telomeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 15 publications
0
18
1
3
Order By: Relevance
“…Twin studies give a heritability factor of similar degree: 60-80% [10,11]. Psoriasis is a heterogeneous disease [12][13][14] and several modes of inheritance have been proposed [1,15]. We have shown that population genetic data for first-degree relatives are compatible with an autosomal recessive mode of inheritance with a gene frequency of 0.25 for a major gene [3,16].…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Twin studies give a heritability factor of similar degree: 60-80% [10,11]. Psoriasis is a heterogeneous disease [12][13][14] and several modes of inheritance have been proposed [1,15]. We have shown that population genetic data for first-degree relatives are compatible with an autosomal recessive mode of inheritance with a gene frequency of 0.25 for a major gene [3,16].…”
Section: Introductionmentioning
confidence: 53%
“…Replicate studies failed to show linkage to the chromosome 4q region [18,19]. The region on chromosome 17 has been confirmed by one group [19] while other studies have failed to replicate the reported linkage [13,18]. Trembath et al [18] reported a genome scan on 66 affected sib pairs through which the authors had identified four potential psoriasis susceptibility loci, on chromosome 2p, chromosome 6p, chromosome 8q and chromosome 20p.…”
Section: Introductionmentioning
confidence: 90%
“…However, in recent years, there has been evidence – some of it conflicting – concerning possible linkage between psoriasis and other loci, notably, loci on chromosomes 4q and 17q. Concerning 17q, some studies [7, 8, 12] have reported positive evidence, whereas others [3, 9, 10] have reported negative evidence. Concerning 4q, Matthews et al [11] have reported positive, and Trembath et al [3] negative evidence.…”
Section: Discussionmentioning
confidence: 96%
“…The strongest candidate for location of a psoriasis susceptibility gene has been a region on chromosome 6p, near the HLA complex, because of the strong, consistent associations reported between psoriasis and certain HLA alleles, particularly B17 and Cw6 [4, 5, 6]. Other possible locations have been reported, particularly on chromosomes 17q and 4q, but follow-up reports have been conflicting [3, 7, 8, 9, 10, 11, 12]. Two recent studies have highlighted still other possible candidate regions [3, 12], but these remain to be confirmed or refuted.…”
Section: Introductionmentioning
confidence: 99%
“…Replication studies have been reported supporting the locus on 17q, 13,14 whereas other studies fail to confirm it. 15, 16 Matthews et al 17 reported a second psoriasis gene location on chromosome 4q using a dominant model with reduced penetrance. No other study has been able to confirm this locus.…”
Section: Introductionmentioning
confidence: 99%